The Interaction Between Helicobacter pylori and Atopy: Does Inverse Association Really Exist? - ERTEM ŞAHİNOĞLU, DENİZ; AKKOÇ, TUNÇ (WILEY, 2009)
To date, cross-sectional and case-control studies suggest an inverse association between Helicobacter pylori infection and atopic diseases, whereas the immunologic basis has not been studied yet. In this study we investigated T helper (Th) cell function in H. pylori-infected children and compared cytokine responses in atopic and non-atopic groups. The study groups was recruited from a cohort of 327 healthy children evaluated and followed-up for 6 years to assess the natural history of H. pylori infection. Seventy-four of 136 healthy children who underwent C-13 urea breath test were eligible and accepted to participate. All participants were evaluated by a questionnaire, and skin-prick testing. According to the results, children were divided into four groups with respect to the presence or absence of H. pylori and atopy. Peripheral blood mononuclear cells isolated from 34 of 74 children were cultured with H. pylori, Der p 1, and phytohemagglutinin (PHA). Interferon-gamma (IFN-gamma), interleukin (IL)-4 and IL-10, transforming growth factor-beta (TGF-beta) levels were measured in supernatants. The frequency of atopy was lower in H. pylori-infected group (31.9% vs. 48.1, p = .22), while atopic symptoms were similar between infected and non-infected children. While PHA and H. pylori induced IFN-gamma levels were significantly higher in H. pylori-infected children, concomitant presence of both atopy and H. pylori decreased the level of PHA and H. pylori induced IFN-gamma production. PHA and Der p 1-induced IL-4 levels were higher in atopic children, and IL-4 production was suppressed when they were concomitantly infected with H. pylori. The production of TGF-beta was found to be suppressed in atopic children irrespective of the presence of H. pylori infection. The results of the current study demonstrated a counteractive Th1 and Th2 cytokine interaction between H. pylori infection and atopy. However, this counteractive immunologic balance did not protect against atopy.
Keywords: Helicobacter pylori; atopy; children; cytokine; lymphocyte culture; REGULATORY T-CELLS; GASTRIC-MUCOSA; INFECTION; CHILDREN; ASTHMA; MODULATION; CHILDHOOD; RESPONSES; DISEASE